A facile way to synthesize a photocrosslinkable methacrylated chitosan hydrogel for biomedical applications. Issue 10 (3rd July 2021) - Samani, Saeed; Bonakdar, Shahin; Farzin, Ali; Hadjati, Jamshid; Azami, Mahmoud
Abstract: In this study, we introduced a novel and modified method to synthesize photocrosslinkable chitosan hydrogel. Three methacrylated samples under two concentrations of methacrylic anhydride and using EDC/NHS as a crosslinker were prepared. Methacrylated chitosan obtained under controlled conditions and using EDC/NHS had significant coupling efficiency and capacity of gel formation compared to other samples. Diluted culture media provided a favorable solubility condition for methacrylated chitosan and could be tolerated by cells during gelation time. The hydrogels included interconnected pores ranging 100–300 µm and swelling ratios of 40–400%. The results opened the new aspects for developing novel biomaterials in cell-based therapies. Graphical Abstract: